The Antibacterial Activity of Chitosan from Haruan (Channa striata) Fish Scales on the Growth of Streptococcus sanguinis - Wijayanti Diah Wasi Hutami; Deby Kania Tri Putri; Amy Nindia Carabelly; Indah Listiana Kriswandini; Ariyati Retno Pratiwi; Muhammad Luthfi (Journal of Indonesian Dental Association, 2020)
Introduction: Recurrent Aphthous Stomatitis (RAS) is the most common oral lesion in Banjarmasin, with a prevalence of 45.42%. Streptococcus sanguinis (S. sanguinis) is thought to be one of the factors causing RAS. One natural ingredient that is often used by the people of South Kalimantan is the Haruan fish. The high Haruan fish consumption will eventually leave fish scales that have the potential to pollute the environment if not addressed immediately. Fish scales contain chitin, which when deacetylated produces chitosan, which has antibacterial properties. Objectives: The purpose of this study was to determine the effectiveness of the chitosan from the scales of the Haruan fish (Channa striata) at inhibiting S. sanguinis growth. Methods: This study used a randomized pretest-posttest with control group design using five treatments. The five treatments were subjected to liquid dilution using the UV-Vis Spectrophotometer method to obtain minimum inhibitory concentration (MIC) and a solid dilution test using the Total Plate Count method to obtain minimum bactericidal concentration (MBC). Results: The results showed that Haruan scale chitosan proved to be effective as an antibacterial against S. sanguinis, with a MIC of 1.25% and a minimum lethal concentration of 2.5%. One-Way Anova test results showed significance for the MIC test (p = 0,000) and MBC test (p = 0.000; p < 0.05). Conclusion: Chitosan from Haruan fish scales is both inhibitory and lethal to S. sanguinis.